Long-term clinical outcome of atrial fibrillation ablation in patients with history of mitral valve surgery - Almorad, Alexandre; O'Neill, Louisa; Wielandts, Jean-Yves; Gillis, Kris; De Becker, Benjamin; Nakatani, Yosuke; De Asmundis, Carlo; Iacopino, Saverio; Pambrun, Thomas; Marc, La Meir; Jaïs, Pierre; Haïssaguerre, Michel; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Atrial fibrillation (AF) occurs frequently after mitral valve (MV) surgery. This study aims to evaluate the efficacy and long-term clinical outcomes after first AF ablation in patients with prior MV surgery. Methods: 60 onsecutive patients with a history of MV surgery without MAZE referred to 3 European centers for a first AF ablation between 2007 and 2017 (group 1) were retrospectively enrolled. They were matched (propensity‐score match) with 60 patients referred for AF ablation without prior MV surgery (group 2). Results: In group 1, 19 (31.7%) patients had mitral stenosis and 41 (68.3%) mitral regurgitation. 27 (45.0%) patients underwent mechanical valve replacement and 33 (55.0%) MV annuloplasty. After the index ablation, 19 patients (31.7%) from group 1 and 24 (40%) from group 2 had no recurrence of atrial arrythmias (ATa) (p=0.3). After 62 (IQR 48-84) months of follow-up and 2 (IQR 2-2) procedures, 90.0% of group 1 and 95.0% of group 2 patients were in sinus rhythm (p = 0.49). At final follow-up, 28 (46.7%) and 33 (55.0%) patients respectively were off antiarrythmic drugs (p=0.46). ATa recurrence was seen more commonly in patients with prior MV surgery (54% vs 22% respectively, p<0.05). No major complication occurred. Conclusion: Long-term freedom of atrial arrythmias after atrial fibrillation catheter ablation is achievable and safe in patients with history of mitral valve surgery. Alike AF patients without history of mitral valve surgery, repeat procedures are needed to maintain sinus rhythm.